PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN BANDENG PRESTO ( Studi Empiris Pada Bandeng Presto âBONAFIDEâ Semarang ) - Sya Faza Maulana, 12.05.51.0079; Maskur, Ali (Students Journal of Economic and Management, 2018)
This study aims to analyze the influence of Brand Citra, Production Quality and Price Perception Against Purchase of Milkfish Presto Bonafide Decision in Semarang. The sample used in this is research is 100 respondents with sampling technique that Accidental Sampling method. The data which is used is premiere data, the analytical data which is used involving validity test, reliability test, multiple regression linear test, coefficient of determination and hypothesis test involving F test and t test. Based on the data analysis and hypothesis test showed that partially, the service quality variable is positively and significantly affected on the purchasing decisions. Price perception variable is positively and significantly affected on the purchasing decisions. Location variable is positively and significantly affected on the purchasing decisions.Keywords: Service Quality, Price Perception, Location and Purchase Decision